GPx-mimetic selenium-enriched yeast nanozymes ameliorate diabetic bone disease via dual-targeting of ROS scavenging and angiogenesis-osteogenesis coupling - Zimei Wu; Qiaodan Hou; Lang Qin; Tingting Chen; Kunkun Yang; Fuxin Wei; Lin Wang (Materials Today Bio)
Diabetic bone disease (DBD) is a severe skeletal complication arising from metabolic dysregulation and redox imbalance during diabetes progression. Its core pathological mechanism involves reactive oxygen species (ROS)-mediated decoupling of angiogenesis-osteogenesis, yet no targeted therapies exist. Herein, we present a biosynthesis strategy to engineer selenium-doped carbon quantum dots (SeYCQDs) from selenium-enriched yeast (SeY) as a bifunctional nanozyme for DBD treatment. By leveraging the bioconversion process of SeY, inorganic selenium is biotransformed into organoselenium metabolites, followed by hydrothermal synthesis to fabricate SeYCQDs with glutathione peroxidase (GPx)-mimetic activity. Mechanistically, under diabetic conditions, SeYCQDs (1) repair mitochondrial membrane potential in vascular endothelial cells (VECs) through GPx-catalyzed ROS scavenging, thereby restoring endothelial function, and (2) activate the VEGF/BMP2/Noggin signaling axis to promote type H vessel (CD31+EMCN+) neovascularization and osteoblast differentiation, thereby sustaining angiogenesis-osteogenesis coupling. This study establishes the first yeast-based nanozyme synchronizing antioxidant defense with metabolic coupling repair, providing a clinically translatable paradigm for diabetes-associated osteometabolic disorders.